Alkyl Lewis Acid Catalyzed Syntheses of Dicarbonyl Ferrocenes - Tombul, M.; Gemici, S.; Bulut, A. (Asian Journal of Chemistry, 2010)
A series of diferrocenoyl compounds; succinyl (1), glutaryl (2), adipoyl (3), suberoyl (4) and sebacoyl ferrocene (5) were synthesized from the reaction of ferrocene with EtAlCl2. Compared to the conventional methods reported in the literature, the yields obtained from these reactions are found to be higher than the typical catalyst.